Measurements of the imploding plasma sheath in triple-nozzle gas-puff z pinches - Lavine, E. S.; Rocco, S. V. R.; Potter, W. M.; Angel, J.; Freeman, E.; Banasek, J. T.; Lawson, J.; Greenly, J. B.; Wilhelm, H.; Hammer, D. A.; Kusse, B. R. (Physics of plasmas, 2022)
Gas-puff z-pinch implosions are characterized by the formation of a dense annular plasma shell, the sheath, that is driven to the axis by magnetic forces and therefore subject to the magneto-Rayleigh–Taylor instability. Here, the conditions within these sheaths are measured on the 1-MA COBRA generator at Cornell University [Greenly et al., Rev. Sci. Instrum. 79, 073501 (2008)] for various gas species and initial fill densities. The gas-puff loads are initialized by a 7 cm diameter triple-nozzle gas valve assembly with concentric outer and inner annular nozzles and a central gas jet. Thomson scattering and laser interferometry provide spatially resolved flow, temperature, and electron density profiles midway through the implosion, while extreme ultraviolet pinhole cameras record the evolution of the plasma column and photoconducting diodes measure x-ray emission. Analysis of the scattering spectra includes a means of discriminating between thermal and non-thermal broadening to test for the presence of hydrodynamic turbulence. Two types of sheath profiles are observed, those with sharp discontinuities at the leading edge and those with smooth gradients. In both cases, non-thermal broadening is generally peaked at the front of the sheath and exhibits a characteristic decay length that roughly scales with the sheath ion mean free path. We demonstrate that this non-thermal broadening term is inconsistent with laminar velocity gradients and is more consistent with dissipative turbulence driven by unstable plasma waves in a collisionless shock. The resulting differences in sheath profile are then set by the sheath ion collisionality in a manner consistent with recent 1D kinetic simulations [Angus et al., Phys. Plasmas 28, 010701 (2021)].